The emergency department approach to violently injured patient care: a regional survey. Issue 4 (4th August 2005) - Wilkinson, D L; Kurtz, E M; Lane, P; Fein, J A
Abstract : Objective: Since the early 1990s public health workers have challenged healthcare practitioners to take an active role in violence prevention with patients aged 10–24 years. Emergency department (ED) clinicians are uniquely positioned to identify, assess, and refer youth involved in violent events. The objective of this study was to describe ED directors' estimate of the number of violently injured youth seen, the presence of established protocols or guidelines for handling youth violence, and the type of training programs offered to ED physicians regarding this issue. Methods: The authors conducted a survey of EDs (n = 64) in the Philadelphia metropolitan region to determine the standard of ED care for violently injured youths. Half of the EDs were in urban areas and half in suburban. Results: A total of 41 out of 64 (64.1%) ED directors completed and returned the written questionnaire. In addition to treating the specific injuries sustained, ED responses to youth violence primarily involved talking with patients about the events surrounding the injury. The estimated number of violently injured youth seen per month varied considerably. Twenty four directors (58.5%) estimated that their institution treated fewer than 10 per month; 10 (24.4%) reported 11–30, and seven (17.1%) mostly large urban hospitals, saw more than 30 per month. Although most hospitals reported that the staff counsels patients about safety concerns, only 17% offered their staff formal training programs on youth violence. Conclusions: To address the prevention of youth violence, EDs need specific training programs for ED staff, as well as systematic risk assessment and referral resources for structured intervention and follow up.